The Poetics of Grief: Analyzing the Narrative of Loss and Advocacy in the 'Curhat Bang' Interview with Sharon ‘Timothy Mother’ - Nabila, Bella; Azhari, Jihan; Rosalinah, Yanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This article investigates the representation of grief and trauma in Indonesia's digital media landscape, with a particular focus on the role of podcasts as a new space for personal narratives and social advocacy. This study analyzes in-depth an interview with Sharon, the mother of the late Timothy Anugerah Saputra, in a high-profile episode of the podcast "Curhat Bang." Using Gérard Genette's conceptual framework of narratology—specifically the concepts of sequence (analepsis), voice, and mood (focalization) as recontextualized by contemporary narrative theorists—this study examines how personal accounts of loss are strategically constructed. The qualitative analysis reveals that the interview effectively uses disrupted chronology (analepsis or flashback) to build emotion and dramatic tension. The first-person perspective, focused on the mother, not only creates intimacy and authenticity but also places the listener directly in the experience of her suffering. The strategic deployment of pathos (emotional appeal) through the mother's voice elevates this personal story into a universal commentary on systemic injustice and the ongoing struggle to attain truth. This transformation transformed journalistic reporting into a powerful tragic narrative, one that not only evoked public empathy but also mobilized calls for justice. Ultimately, this analysis offers significant insights into the intersections between grief narratives, media genres, and advocacy, and demonstrates the transformative power of digital storytelling in shaping public discourse in contemporary Indonesia.